The New Nutrition Facts Label - Samantha Buddemeyer; Gail P. A. Kauwell (EDIS)
The Nutrition Facts label is a great tool for consumers who are trying to make better food choices; it was created in 1993 to help members of the public learn more about the nutritional value of their food. Revisions to the label’s design were released in 2016, marking the first major change to the label in over 20 years. This 3-page document, written by Samantha Buddemeyer and Gail P. A. Kauwell, discusses the new features of the Nutrition Facts label. Published by the UF/IFAS Department of Food Science and Human Nutrition, January 2018. http://edis.ifas.ufl.edu/fs300